Case report: Comprehensive follow-up of a Colombian family carrying a novel MEN1 variant linked to a rare ACTH-producing pancreatic neuroendocrine carcinoma - Riaño-Moreno, Julián C.; González-Clavijo, Angélica María; Torres J., William C.; Medina B., Vilma L.; Romero-Rojas, Alfredo Ernesto; Vieda-Celemin, Isabella; Avila-Moya, Jordan A.; Baron-Cardona, Johan A.; Bravo-Patiño, Juan P.; Torres-Zambrano, Oscar S.; Maya, Luis Felipe Fierro (Frontiers in Endocrinology, 2024)
Background: Multiple Endocrine Neoplasia type 1 (MEN1) is an autosomal dominant disorder marked by pathogenic variants in the MEN1 tumor suppressor gene, leading to tumors in the parathyroid glands, pancreas, and pituitary. The occurrence of ACTH-producing pancreatic neuroendocrine carcinoma is exceedingly rare in MEN1.Case Presentation: This report details a Colombian family harboring a novel MEN1 variant identified through genetic screening initiated by the index case. Affected family members exhibited primary hyperparathyroidism (PHPT) symptoms from their 20s to 50s. Uniquely, the index case developed an ACTH-secreting pancreatic neuroendocrine carcinoma, a rarity in MEN1 syndromes. Proactive screening enabled the early detection of pituitary neuroendocrine tumors (PitNETs) as microadenomas in two carriers, with subsequent surgical or pharmacological intervention based on the clinical presentation.Our findings underscore the significance of cascade screening in facilitating the early diagnosis and individualized treatment of MEN1, contributing to better patient outcomes. Additionally, this study brings to light a novel presentation of ACTH-producing pancreatic neuroendocrine carcinoma within the MEN1 spectrum, expanding our understanding of the disease's manifestations.